Cytosolic peroxidases protect the lysosome of bloodstream African trypanosomes from iron-mediated membrane damage - Schaffroth, Corinna; Nißen, Amrei; Benítez, Diego; Comini, Marcelo A.; Krauth-Siegel, Renate (PLoS pathogens, 2014)
African trypanosomes express three virtually identical non-selenium glutathione peroxidase (Px)-type enzymes which preferably detoxify lipid-derived hydroperoxides. As shown previously, bloodstream Trypanosoma brucei lacking the mitochondrial Px III display only a weak and transient proliferation defect whereas parasites that lack the cytosolic Px I and Px II undergo extremely fast lipid peroxidation and cell lysis. The phenotype can completely be rescued by supplementing the medium with the α-tocopherol derivative Trolox.